Pengaruh Pelatihan Kerja Dan Kesehatan Keselamatan Kerja Terhadap Kinerja Karyawan Di Summarecon Mall Kelapa Gading - Dea Wahyuni; Novita Wahyu Setyawati; Indah Rizki Maulia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to determine the Effect of Job Training and Occupational Health and Safety (K3) on Employee Performance at Summarecon Mall Kelapa Gading. This study uses a quantitative research method. In the specified sample, the author uses the Slovin Formula and the sample used is 88 SMKG employee respondents whose work is related to K3. Testing was carried out using SPSS software version 26. The results of the research that has been carried out are that both partially and simultaneously job training and occupational health and safety have a positive and significant effect on employee performance